GOOD GOVERNANCE DALAM PENGELOLAAN USAHA KECIL DAN MENENGAH - Eko Suyono; Sugiarto *; Mafudi *; Taufik Hidayat (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
SMEs are a type of business that generally dominates in developing countries including Indonesia. So it can be said that SMEs are the main pillar of a country's economy, which contributes dominantly in supporting the state income. In general, the managers or owners of SMEs run their business in a rudimentary manner without accompanied by good corporate governance concepts. Good corporate governance today is seen as an important indicator of a stable economy. This will help to protect the rights and interests of shareholders and all other stakeholders, providing a framework for monitoring the actions and performance of management effectively and to drive better business results. In general, however, good corporate governance concepts are applicable to large corporations, so it needs a media to translate the concepts of good corporate governance from large companies to SMEs. One of the frameworks and such codes may not reflect the characteristics of SMEs, where in the SMEs, owners may also be the managers, or where company ownership can be shared across family members. But in general, for SMEs, corporate governance primarily is to improve business efficiency and performance, and less monitor management actions. So with the implementation of good governance in SMEs, it is expected that this type of business will grow and become more professional in sustaining the country economy.